2011
DOI: 10.1103/physrevd.83.024001
|View full text |Cite
|
Sign up to set email alerts
|

Poincaré gauge theory of gravity: Friedman cosmology with even and odd parity modes: Analytic part

Abstract: We propose a cosmological model in the framework of the Poincaré gauge theory of gravity (PG). The gravitational Lagrangian is quadratic in both curvature and torsion. In our specific model, the Lagrangian contains (i) the curvature scalar R and the curvature pseudoscalar X linearly and quadratically (including an RX term) and (ii) pieces quadratic in the torsion vector V and the torsion axial vector A (including a V A term). We show generally that in quadratic PG models we have nearly the same number of parit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
111
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(113 citation statements)
references
References 108 publications
2
111
0
Order By: Relevance
“…Recently, however, there has been a growing interest for the extended class of models with a general Lagrangian that includes both parity even and parity odd quadratic terms, see for instance [18][19][20][21][22][23]. An important difference between these two classes of PGT models is manifest in their particle spectra.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, however, there has been a growing interest for the extended class of models with a general Lagrangian that includes both parity even and parity odd quadratic terms, see for instance [18][19][20][21][22][23]. An important difference between these two classes of PGT models is manifest in their particle spectra.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the effects of spin tensor in the large-scale dynamics of the universe will only be relevant at the very early times. However, one should note that due to the fundamental difference between the field equations of PGT and their general relativistic counterparts, torsion can also effects the late-time dynamics of the universe, as has been shown in [5,8,23,24] One of the most important tests for any inflationary model is its ability to generate nearly scale-invariant spectrum of scalar perturbations at the end of inflation. The scalar spectral index is given by [27] …”
Section: A Numerical Resultsmentioning
confidence: 99%
“…Here we show that in PGT using the Lagrangian in the form of (11), the effects of spin and torsion cause the Universe to enter an inflationary epoch with a wide range of parameters. Also, using the assumption of vanishing spin tensor at late times, it has been shown that Poincaré gauge theory of gravity is also able to explain present time accelerated expansion of the universe [5,8,[23][24][25].…”
Section: Dynamics Of Early Universe and Inflationary Epochmentioning
confidence: 99%
See 1 more Smart Citation
“…We focus on the case including a pseudoscalar scalar torsion function f as suggested by Baekler, Hehl and Nester [98]. The gravitational field equation and the two-family cosmological equations has been obtained in ref.…”
Section: Jhep05(2016)024 6 Conclusionmentioning
confidence: 99%